Simultaneously mechanically flexible, photobending, and acidochromic cyanostilbene molecular crystals - Parthasarathy, Thiyagaraj; Mishra, Manish Kumar; Bhattacharya, Biswajit; Emmerling, Franziska; Ghosh, Soumyajit (Crystal Growth & Design, 2024)
Molecular crystals that respond to multiple stimuli are gaining significant attention for their potential in smart materials like actuators and sensors. However, imparting multiple stimuli-responsive properties to a single crystal remains a major challenge. Herein, we report two cyanostilbene derivative-based crystals 1 and 2, with various responses to stimuli such as mechanical stress, light, acid vapors, etc. Both crystals 1 and 2 demonstrated mechanical flexibility and reversible acidochromism. Additionally, crystal 1 also exhibited light-induced photobending, which is ascribed to Z to E photoisomerization. Detailed structure-property correlation was established to unravel distinct mechanical responses. The development of these multitasking crystals may find applications in multitasking actuators, anticounterfeiting materials, and more.